2018
DOI: 10.1093/jpids/piy019
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Prescribing Antimicrobials for Prophylaxis in Children and Neonates: Results From the Antibiotic Resistance and Prescribing in European Children Point Prevalence Survey

Abstract: A high proportion of hospitalized children received prophylactic BSAs. This represents a clear target for quality improvement. Collectively speaking, it is critical to reduce total prophylactic prescribing, BSA use, and prolonged prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 11 publications
5
27
0
4
Order By: Relevance
“…A recent cross-sectional study reported that nearly one-third (32.9%) of European children's hospital inpatients received an antibiotic for prophylactic use (73.4% for medical diseases and 26.6% for surgical diseases). 16 Another study previously assessed antibiotic use in children admitted to hospitals participating in PHIS in 2008, before widespread implementation of inpatient antibiotic stewardship initiatives, and reported that~60% of hospitalized children received antibiotics at some point during their hospital stay as well as similar regional variability to that observed in our current study. 15 Differences in study design and measurement approaches likely account for some of the differences between the results of that study and our observed prevalence of 36.6%; our cross-sectional study focused on a single point-in-time assessment.…”
Section: Discussionsupporting
confidence: 80%
“…A recent cross-sectional study reported that nearly one-third (32.9%) of European children's hospital inpatients received an antibiotic for prophylactic use (73.4% for medical diseases and 26.6% for surgical diseases). 16 Another study previously assessed antibiotic use in children admitted to hospitals participating in PHIS in 2008, before widespread implementation of inpatient antibiotic stewardship initiatives, and reported that~60% of hospitalized children received antibiotics at some point during their hospital stay as well as similar regional variability to that observed in our current study. 15 Differences in study design and measurement approaches likely account for some of the differences between the results of that study and our observed prevalence of 36.6%; our cross-sectional study focused on a single point-in-time assessment.…”
Section: Discussionsupporting
confidence: 80%
“…Prophylaxis in pediatric surgical wards, however, accounted for 68.1% of antibiotic prescriptions. This was much higher than the percentage of antibiotic prophylaxis for surgical diseases in the treatment of children in Europe (26.6%) [ 29 ]. Also, 30% of the children in surgical wards in this study received two or more types of antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…gibt [15]. Mehr als die Hälfte aller operierten Kinder erhält statt einer einmaligen präoperativen Gabe eines Antibiotikums eine "PAP", die länger als 24 h verabreicht wird.…”
Section: Perioperative Antibiotikaprophylaxeunclassified